Research on the Development of Public Administration in Lithuania - Guogis, Arvydas; Gudelis, Dangis; Smalskys, Vainius; Rakšnys, Vincas Adomas; Sukvietiene, Ausra; Reinholde, Iveta (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Research conducted on public administration in Lithuania covers various subjects related to different fields and activities within the public sector. However, most research focuses only on challenges associated with the civil service and local self-government in Lithuania. This research aims to define public administration research and improve understanding of the progress and trajectory of contemporary public sector research in Lithuania. The research methods include document analysis, qualitative descriptive approaches, and historical data analysis. Moreover, the triangulation method verifies research results by integrating data and observations from many sources. The research results found that in the development of public law in Lithuania, researchers in the field of Lithuanian public administration focused on the goals of government reform, civil service modernization, creative solutions, and trends and reforms in central and regional administration. They also concentrate on social policy procedures, improving public governance, and intelligent examination of public administration. Lithuanian authors also focus on improving public governance through the use of the concepts of cooperation, participation, and teamwork. The study of Lithuanian public administration is closely related to the evolution of traditional public administration, focusing on evaluating new public management practices and implementing various public management innovations in government sector organizations since the start of state restoration. Future directions of public administration research in Lithuania will focus on addressing the challenges faced by the public sector and society in other countries. These challenges include sustainable development, climate change, gender equality, and other contemporary issues that directly or indirectly impact the public sector.